Factors that Influence the Behavior of Women of Childbearing Age (WUS) for Early Detection of Cervical Cancer Through IVA Tests in Indonesia: Literature Review - Gerda Angela Komalawati; Evi Martha (International Journal Labs, 2023)
Cervical cancer is the second largest cancer in Indonesia after breast cancer with an estimated number of new cases of 32,469 (17.2%). Meanwhile, the coverage of early detection of cervical cancer is still far below the target, namely 10.4%, which is ideally 80%. As many as 70% of cervical cancer cases are found to be in an advanced stage, thereby increasing mortality in women. This indicates that women still have low interest in early detection of cervical cancer, namely using the IVA (Visual Inspection with Acetic Acid) method. This literature review aims to determine the factors that influence the behavior of women of childbearing age (WUS) for early detection of cervical cancer through the IVA test. This literature review uses Literature reviews such as articles in research journal databases, searches are carried out via the internet in the form of reviewing articles via Google Scholar. From the initial search results using keywords, 240 articles were obtained and after carrying out the inclusion and exclusion criteria, 9 articles were obtained that were relevant to the publication period starting from 2018-2022. From some of the literature, it was found that the factors that influence WUS behavior for early detection of cervical cancer through the IVA test are influenced by knowledge, attitudes, husband/family support, access and sources of information, access to health services supported by cadres and health workers and culture of shame and fear. knowledge and attitudes of WUS, husband's support, support from health workers, and access to information sources. All factors have a very important role in influencing the behavior of WUS in carrying out VIA examinations. To motivate WUS to carry out IVA, health workers can increase health education regarding cervical cancer and early detection of cervical cancer to husbands and WUS with attractive media to attract the interest and participation of WUS to participate in VIA tests to reduce the morbidity and mortality rates for cervical cancer in Indonesia.